2023
DOI: 10.3390/polym15204190
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a Fish-Bone-Inspired Inorganic–Organic Composite Membrane

YuYang Jiao,
Masahiro Okada,
Bhingaradiya Nutan
et al.

Abstract: Biological materials have properties like great strength and flexibility that are not present in synthetic materials. Using the ribs of crucian carp as a reference, we investigated the mechanisms behind the high mechanical properties of this rib bone, and found highly oriented layers of calcium phosphate (CaP) and collagen fibers. To fabricate a fish-rib-bone-mimicking membrane with similar structure and mechanical properties, this study involves (1) the rapid synthesis of plate-like CaP crystals, (2) the laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Reportedly, some HCMs have been fabricated with additional inorganic or hybrid fillers. Additives can be incorporated into hydrogel matrixes to enhance their mechanical, dielectric, and antifouling properties or thermal stability. For example, Ali et al showed that the addition of Al 2 O 3 and SiO 2 fillers to PVA/PVP HCMs enhances the dielectric properties. On the other hand, calcium phosphorus (CaP) fillers improved the mechanical properties of gelatin membranes .…”
Section: Advances In Membrane Dewateringmentioning
confidence: 99%
See 2 more Smart Citations
“…Reportedly, some HCMs have been fabricated with additional inorganic or hybrid fillers. Additives can be incorporated into hydrogel matrixes to enhance their mechanical, dielectric, and antifouling properties or thermal stability. For example, Ali et al showed that the addition of Al 2 O 3 and SiO 2 fillers to PVA/PVP HCMs enhances the dielectric properties. On the other hand, calcium phosphorus (CaP) fillers improved the mechanical properties of gelatin membranes .…”
Section: Advances In Membrane Dewateringmentioning
confidence: 99%
“…Additives can be incorporated into hydrogel matrixes to enhance their mechanical, dielectric, and antifouling properties or thermal stability. For example, Ali et al showed that the addition of Al 2 O 3 and SiO 2 fillers to PVA/PVP HCMs enhances the dielectric properties. On the other hand, calcium phosphorus (CaP) fillers improved the mechanical properties of gelatin membranes . Silver–polydopamine (Ag–PDA) nanospheres were coated onto a PSF support to enhance the water flux and antibacterial properties while maintaining a good antifouling membrane surface .…”
Section: Advances In Membrane Dewateringmentioning
confidence: 99%
See 1 more Smart Citation